Results of the pedagogical experiment on the development of inclusive competence of teachers of general education organisations - Mirgul Esengulova; Zamira Dzhaparova; Bermet Asanbaeva; Barisa Turdubaeva (Social Sciences and Humanities Open)
The purpose of the study was the practical implementation of the developed model of formation of inclusive competence necessary for work in the pedagogical environment. The basis for the study was an experiment, during which the author's module “Developing the level of inclusive competence of teachers” was used among employees of general educational organisations (180 people). The model consisted of the following components: target component, content-processual, and evaluation-result. The effectiveness of the developed methodology was tested by comparing the results of pre-test and post-test of the experimental (85 people) and control (95 people) groups. The findings indicated that participants in the experimental group had a markedly superior proficiency in inclusive education following the workshops, in contrast to the control group. This result supports the application of the established approach as a professional development initiative for educators. The study revealed that some educators continue to feel insufficiently equipped to execute inclusive policies. They articulated concerns over their insufficient understanding and confidence in their capacity to work with kids with special educational needs. These findings demonstrate an ongoing necessity for a more comprehensive plan to execute inclusive policies inside the educational system. The research highlights how effective the training program is while also stressing the need for better teacher preparation and support from schools for inclusive education. The research underscores the efficacy of the training module while also emphasising the necessity for enhanced educator preparation and institutional backing for inclusive education.